Graphene-like film CVD on e-beam exposed SiO2/Si by the pyrolysis of different oxygen-containing precursors. Issue 4 (2nd April 2020) - Sedlovets, Daria M.; Knyazev, Maxim A.; Trofimov, Oleg V.; Koveshnikov, Sergei V.
ABSRTACT: We have previously found that pyrolysis of ethanol vapor on charge pre-patterned SiO2 /Si substrate leads to controllable deposition of graphene-like films (GLFs). In this work we aim at the GLFs synthesis from acetone and isopropanol on SiO2/Si exposed to an electron beam with various energies and doses. Electron beam induced charge in 200 nm SiO2 is determined by the shift of the capacitance-voltage characteristics. Synthesized GLFs are characterized using Raman spectroscopy and atomic force microscopy. It is shown that the thickness of GLF on SiO2 /Si increase together with the preliminary exposure dose and inversely associated with electron energies.